Profile of Patients With Respiratory Failure at Pediatric Intensive Care Unit (PICU) Dr. Soetomo General Hospital - Cindy Aprilia Eka Prasanty; Arina Setyaningtyas; Arie Utariani (Faculty of Medicine-Universitas Airlangga, 2021)
Introduction: Respiratory failure is the respiratory system's inability to maintain its gas exchange functions, oxygenation, and carbon dioxide elimination. Infant and children are more susceptible to develop respiratory failure. Respiratory failure can also be caused by several diseases/conditions, which is a common reason for pediatrics to be admitted to the intensive care unit. Objective: This study aims to describe patients' demographic and clinical profile with respiratory failure at the PICU of Dr. Soetomo General Hospital, Surabaya. Materials and Methods: This is a prospective study with the descriptive method using the medical records of patients with respiratory failure who were admitted to the PICU from September 2019 to February 2020 and had arterial BGA data (PaCO2, PaO2), which were examined in the PICU or resuscitation room before the patients were admitted to the PICU. Results: This study showed that out of 35 patients, 24 (68.6%) were female, 19 (54.3%) were <1 year old, and 20 (57.1%) had normal nutritional status. Type I (hypoxemic) and type II (hypercapnic) respiratory failures were found in 13 patients (37.1%), respectively. The most common clinical signs were fever in 26 patients (74.3%), shortness of breath in 24 patients (68.6%), and chest retraction in 24 patients (68.6%). The primary diagnosis that commonly occurred was respiratory system disorders in 15 patients (42.9%). The other diagnosis that mainly occurred was nutrition and metabolic disorders of 19 patients (54.3%). The patients' outcome was that 24 patients were survived (68.6%), and ten patients died (28.6%). Conclusions: Various clinical signs and diagnoses can be found in patients with respiratory failure at PICU. The most common respiratory failure types are type I (hypoxemic) and type II (hypercapnic) respiratory failure.